SOME CHARACTERISTICS OF ATMOSPHERIC BOUNDARY LAYER OVER MAKASSAR - Assegaf, Alimuddin Hamzah; Samad, Wasir; Sakka, Sakka (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Some upper air atmospheric parameters measured during period of 2011-2016 by means of radiosonde located at Hasanuddin International Airport were examined for characterization of boundary layer over Makassar, Indonesia. These data, combined with surface atmospheric parameters were used to calculate some boundary layer parameters using AERMET model which based on Monin-Obukhov similarity theory. The obtained Monin-Obukhov length which reflecting atmospheric stability then converted into traditional Pasquill-Gifford stability classification. Examination of wind characteristics of wind showing clearly their dependence of the day, season and height. Winds dominantly flows from the southeast during the daytime with the relatively larger velocity and from the northwest with smaller velocity during the nighttime. Interpretation of monin-obukhov length using Pasquill-Gifford stability classification showing that the atmosphere was dominantly unstable during the daytime and dominantly stable during the nighttime. These atmospheric stabilities were also varied during seasons. The height of convective boundary layer (CBL) was start to rise in the morning and reaching its maximum in the afternoon (18:00) at the mean value of 2 km. Meanwhile, the height of mechanical boundary layer (MBL) during the day time forming parabolic curve with its maximum value of 1.2 km at noon. These indicated that any released pollution from the stack will be less dispersed during the nighttime due to the fact of lower mixing height, lower wind speed, atmosphere become more stable, and it dispersed in different direction compare to the daytime.